Asbestos Exposure and Ovarian Cancer – a Gynaecological Occupational Disease. Background, Mandatory Notification, Practical Approach - Nowak, Dennis; Schmalfeldt, Barbara; Tannapfel, Andrea; Mahner, Sven (Geburtshilfe und Frauenheilkunde, 2021)
In 2017, ovarian cancer due to asbestos exposure was designated a new, and thereby the first, gynaecological occupational disease in Germany. Asbestos is a naturally occurring mineral fibre with an annual usage in Germany of 160 000 – 180 000 metric tonnes in the 1960s and 1970s. The carcinogenicity of asbestos for the target organs lungs, larynx, pleura including pericardium, and peritoneum including tunica vaginalis testis has been clearly established for many years. Recent meta-analyses of data from cohort studies have demonstrated that the risk of ovarian cancer roughly doubles in women with occupational exposure to asbestos. Since the group of people with double the risk of developing lung cancer due to work-related asbestos exposure has a 2.25-fold increased risk of mortality from ovarian cancer on average, work-related ovarian cancer has been assigned the same recognition requirements as in occupational lung (and laryngeal) cancer. Thus, gynaecologists must obtain a thorough history of occupational exposure to asbestos, even if it may have taken place long in the past. The law mandates that suspected such cases must be reported to the Statutory Accident Insurance carrier or the State Occupational Safety and Health Agency.Seit 2017 gibt es eine neue, die erste gynäkologische Berufskrankheit, das Ovarialkarzinom durch Asbest. Asbest ist ein natürlich vorkommender mineralischer Faserstoff mit einem Verbrauch von 160 000 – 180 000 Tonnen jährlich in den 1960er- und 1970er-Jahren in Deutschland. Die Karzinogenität von Asbest für die Zielorgane Lunge, Larynx, Pleura einschließlich Perikard sowie Peritoneum einschließlich Tunica vaginalis testis ist seit vielen Jahren eindeutig gesichert. Neuere Metaanalysen von Daten aus Kohortenstudien zeigen, dass sich das Ovarialkarzinomrisiko bei Frauen etwa verdoppelt, die beruflichen Umgang mit Asbest hatten. Da die Personengruppe, bei der das Verdoppelungsrisiko für die Entstehung eines Lungenkarzinoms durch arbeitsbedingte Asbestexposition gegeben ist, ein im Mittel 2,25-fach erhöhtes Risiko für die Mortalität an einem Ovarialkarzinom aufweist, wurden für das berufsbedingte Ovarialkarzinom dieselben Anerkennungsvoraussetzungen wie für das berufsbedingte Lungen- (und Larynxkarzinom) festgelegt. Somit muss der Gynäkologe eine Arbeitsanamnese bezüglich langjährig zurückliegender beruflicher Asbestexposition erheben. Eine Meldepflicht des Verdachts an Unfallversicherungsträger oder Staatlichen Gewerbearzt ist gesetzlich vorgeschrieben.
Keywords: ovary; ovarian cancer; occupational disease; asbestos